Euphemisms in the Handling of the Dead in Sarawak Malay Community: A Cognitive Semantic Analysis): (Eufemisme Pengurusan Jenazah Masyarakat Melayu Sarawak: Analisis Semantik Kognitif) (Jurnal Bahasa, 2016)
This paper investigates the use of euphemisms by the Malay community of Sarawak in death-related matters, particularly in the handling of the dead. Data was collected through interviews, recordings and observations involving informants in Kuching, Sarawak. The data was analysed using Lakoff's (1987) Cognitive Semantic framework. Several cognitive mechanisms were used to analyse the data such as image schema, conceptual metaphor, and metonymy. Results reveal that the conceptualisations of death euphemisms in Sarawak Malay are largely influenced by their language culture, which emphasises courtesy and decorum in communication. Additionally, adherence to Islam underlies their thinking and daily practices, and are embedded within these euphemisms. This scenario demonstrates that the Sarawak Malays make use of a specific language form in communicating matters related to death, particularly in the handling of the dead. This study focuses on the cognitive semantics aspect in investigating death euphemisms in Sarawak Malay.Keywords: euphemism, Sarawak Malays, death, cognitive semantics, culture